Detection and identification of power switch failures for fault-tolerant operation of flying capacitor Buck-boost converters. (September 2018) - Tang, Sai; Yin, Xin; Wang, Daming; Zhang, Chao; Shuai, Zhikang; Yang, Xin; Shen, Z. John; Wang, Jun
Abstract: Power switch failures have great influence for electronic converter. Prompt detection of power switch's failure and fault-tolerant operation of multilevel converters have extremely vital significance for high reliability electronic systems. The paper presents a new technique of detecting, identifying, and locating faults of switching devices in an N-Level Flying Capacitor Buck-Boost Converter (FCBBC). The characteristics of inductor current and flying capacitor voltage of FCBBC with different kinds of failure are analyzed. A new fault diagnosis algorithm is proposed to detect and identify the fault on basis of this information. Then the fault-tolerant operation method of the FCBBC is also discussed. The validity of the new control method is demonstrated in the control hardware by experiment result. Highlights: Summarizes the Changed trend of the circuit parameters of multilevel converter when power switches fail A new fault diagnosis algorithm with high precision and speed is proposed for a FCBBC Converters Reform the Flying Capacitor Buck-Boost Converters so that it can operate in the fault-tolerant state